Membentuk Identitas Islami di Tengah Tantangan Era Milenial; Pendekatan dan Strategi Pembelajaran Islam - Nasaruddin, Nasaruddin; Safrudin, Moh. (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
In the millennial era, Muslim youths are often exposed to diverse worldviews and cultural influences originating from an increasingly pluralistic and global environment. Shifts in social values, increased mobility, and developments in communication technology open up greater access to information and different perspectives. This study aims to understand the challenges faced in forming an Islamic identity in the millennial era and to seek approaches and strategies for learning the Islamic religion that are effective in addressing these challenges. The research methodology used is library research, analyzing several sources from books, magazines, journals and other sources. This study will analyze the impact of these factors on Islamic identity and investigate Islamic learning approaches and strategies that can be used to strengthen Islamic identity in the midst of these challenges. Research findings on effective Islamic learning approaches and strategies to help strengthen the millennial generation's Islamic identity in the midst of these challenges. This can include innovative approaches, appropriate use of technology, and approaches that take millennial needs and preferences into account. In this turbulent and changing millennial era, young Muslims face various external influences that can affect the formation of their identity. Factors such as digital technology and social media have a significant influence in building the Islamic identity of the younger generation